2022
DOI: 10.1177/13657127221119545
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood ratios in psychological expert opinion, and their reception by professional judges

Abstract: In various countries, forensic scientists have begun to express their expert opinion in terms of the likelihood of observing the evidence under the primary and under an alternative hypothesis (i.e. the likelihood-ratio approach). This development is often confined to technical domains such as fingerprint analyses. In forensic psychological expertise, likelihood ratios are largely absent. In this contribution, we explain how forensic psychologists can employ likelihood ratios, and we describe two illustrating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, there is an alternative approach that may make the SD4 more useful in this regard, namely the likelihood-ratio approach. This approach is common in forensic sciences 15 and was introduced in forensic psychology recently 16 . Applied to our analysis, findings suggest that liars are approximately six times more likely to score in the range of 27 to 31 (5.4%) than are truth tellers (0.9%).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an alternative approach that may make the SD4 more useful in this regard, namely the likelihood-ratio approach. This approach is common in forensic sciences 15 and was introduced in forensic psychology recently 16 . Applied to our analysis, findings suggest that liars are approximately six times more likely to score in the range of 27 to 31 (5.4%) than are truth tellers (0.9%).…”
Section: Discussionmentioning
confidence: 99%
“…This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.1 Apart from using the smallest effect size of interest, psychological scientists have suggested that the use of likelihood ratios in expert testimony can help in conveying the practical relevance of research(Rassin et al, 2022).…”
mentioning
confidence: 99%
“…1Apart from using the smallest effect size of interest, psychological scientists have suggested that the use of likelihood ratios in expert testimony can help in conveying the practical relevance of research (Rassin et al, 2022). …”
mentioning
confidence: 99%